Frontal wedge variations and controls of submarine landslides in the Negros–Sulu Trench System, Philippines - Nawanao, Lyndon P.; Ramos, Noelynna T. (Frontiers in Earth Science, 2023)
Frontal wedge characteristics provide clues to the efficiency of the overriding slab for large displacement during megathrust and upper-plate earthquakes, whereas submarine landslides along active margins trigger or amplify tsunamis. The lack of clear precursors of submarine failures poses difficulty in monitoring and providing real-time alert warning systems. With that, delineating submarine features along active margins, their spatial distribution, and controls provide valuable information in identifying regions susceptible to large submarine landslides and tsunami hazard assessments. In this study, we performed terrain and morphometric analyses on 20-m resolution bathymetry data to map submarine landslides, submarine canyons, and lineaments in the forearc margin of the Negros–Sulu Trench System, Philippines. Lineaments are distributed mainly along the frontal wedge, where previous seismic surveys revealed that the mapped ridges are morphotectonic expressions of thrusted sediments. The morphological variations of the four frontal wedge segments were attributed to heterogeneous sediment influx, convergence rates, and subduction processes. More than 1,200 submarine landslides and their morphometric parameters were delineated, and exploratory spatial analyses indicate clustering and underlying controls. The tendencies of prolate submarine landslides (high L/W) to significantly cluster along submarine canyons while oblate morphologies (low L/W) along the frontal wedge reflect the different environments and geomorphological conditions to form these contrasting shapes. Ubiquitous small submarine landslides are mainly controlled by submarine canyon systems at relatively shallow depths of <2 km, where high sediment influx from inland sources preconditions instability. Large submarine landslides (> 0.5 km3), on the other hand, are most clustered significantly where the Cagayan Ridge seamount collides and subsequently subducts beneath the northernmost frontal wedge. This suggests the dominant role of seamount subduction and related tectonic processes causing slope steepening to mainly induce large submarine landslides. This study unveiled how submarine landslides vary morphologically depending on their spatial, geomorphological, and tectonic controls in the active margin. This new information provides clues in identifying offshore areas susceptible to large submarine landslides that may induce damaging tsunamis in the NSTS as well as in other active margins of similar underlying controls.